A Review of the Basic Technical Skills of Female Futsal Players - Harry Syahputra Nasution; Annisa Sulistianingsih; Fitriani; Ayu Purnama Wenly (Universitas Negeri Jakarta Postgraduate of Physical Education Departments, 2025)
This study aims to determine the level of basic technical skills among female futsal players at SMA Negeri 1 Bintan Utara. The research employed a descriptive quantitative method. The population of this study consisted of 15 female futsal players, and the sampling technique used was total sampling, meaning that all members of the population were included as research subjects. Data were collected using the Futsal Skills Test instrument developed by FIK Jogja. The data analysis technique applied was descriptive statistics using percentage calculations. The results showed that 3 players (20%) were in the “Excellent” category, 2 players (13.3%) in the “Very Good” category, 2 players (13.3%) in the “Average” category, and 8 players (53.4%) in the “Below Average” category, while no players (0%) were classified as “Failing.” Based on these findings, it can be concluded that the overall level of basic technical skills of female futsal players at SMA Negeri 1 Bintan Utara is categorized as “Below Average.”